PO058 Epilepsy management in the elderly: lessons from nash. (1st December 2017) - Ziso, B; Dixon, P; Marson, AG
Abstract : Objectives: Epilepsy is the third most common neurological diagnosis in the elderly, management remains variable. The National Audit of Seizure management in Hospitals (NASH) set out to assess care provided to patients attending hospitals in the UK. Method: 154 Emergency Departments (EDs) across the UK took part. 1256 patients aged 60 years or over were included for analysis (median age 74 years, 54% men). 51% were known to have epilepsy, 17% had history of previous seizure or blackout and 32% presented with a suspected first seizure. Results: 14% of elderly patients with epilepsy were not on treatment, 59% were on monotherapy. Sodium valproate was the most commonly used antiepileptic (28%). 71% of patients with suspected first seizure and 35% of patients with epilepsy had a CT scan during admission. 34% of those with suspected first seizure were referred to a neurologist on discharge compared to 68% of patients under the age of 60. 52% of 60–69 year olds with a suspected first seizure were referred to neurology compared to 25% of patients aged 80–89. Conclusions: Elderly patients presenting with seizures are less likely to be referred to specialist services on discharge, with significant disparity in patient age and referral rate.